An Alternative Approach for Acetylation of Amine Terminated Polyamidoamine (PAMAM) Dendrimer - Surya Prakash Gautam; Raj K. Keservani; Tapsya Gautam; Arun K. Gupta; Anil Kumar Sharma (Facultad de Farmacia, Universidad de Granada, 2015)
Aim: Polyamidoamine (PAMAM) dendrimers inherent properties have made it the nanocarrier of choice in the current era of innovation. Dendrimer based products are growing and mushrooming like anything in the current time. Although it suffer from hemolytic toxicity which could be reduced by protecting free amino group. Methods: In the present work alternate acetylated method for PAMAM dendrimers was discussed. 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide Linker was used for acetylation. The acetylated conjugate was evaluated for color reaction, Ultraviolet-visible spectroscopy, Fourier Transform infrared spectroscopy, Differential scanning calorimetric, Nuclear magnetic resonance spectra studies. Results: The PAMAM dendrimers were synthesized using divergent approach and further acetylated. Change in λmax values from 282.0 to 282.5 nm was observed for acetylated dendrimers. Characteristic peak of N-H stretch of primary amine at 3284.16 cm-1 was disappeared due to conversion of primary amine to secondary amine. A new peak of -(CO)-NH stretch was obtained at 1640.28 cm-1 (medium) which shows attachment of acetic acid surface group. The changes in Endothermic peak from 120.56 to 110.40ºC were observed which shows the PAMAM dendrimers surface modifications The peak of -NH2 at 2.99 ppm was replaced by (-NHCOCH3) at 2.42 ppm further supports the proof of acetylation. Conclusions: The spectral data clearly revealed that this approach for acetylation gives considerable amount of acetylation in less time duration with elimination of organic solvent. This method could be employed for regular acetylation of amine terminated nanocarriers. EDC linker mediated capping of amine groups opened a new avenue for acetylation of amine terminated protein/peptides.